The Dual Nature of Type I and Type II Interferons - Lee, Amanda J.; Ashkar, Ali A. (Frontiers in Immunology, 2018)
Type I and type II interferons (IFN) are central to both combating virus infection and modulating the antiviral immune response. Indeed, an absence of either the receptor for type I IFNs or IFN-y have resulted in increased susceptibility to virus infection, including increased virus replication and reduced survival. However, an emerging area of research has shown that there is a dual nature to these cytokines. Recent evidence has demonstrated that both type I and type II IFNs have immunoregulatory functions during infection and type II immune responses. In this review, we address the dual nature of type I and type II interferons and present evidence that both antiviral and immunomodulatory functions are critical during virus infection to not only limit virus replication and initiate an appropriate antiviral immune response, but to also negatively regulate this response to minimize tissue damage. Both the activating and negatively regulatory properties of type I and II IFNs work in concert with each other to create a balanced immune response that combats the infection while minimizing collateral damage